O obowiązku alimentacyjnym między rozwiedzionymi małżonkami - Szpunar, Adam (Wydział Prawa i Administracji UAM, 1989)
The Supreme Court's Guidelines of Dec. 16, 1987 encourage to examine once again some basic questions concerning the duty of alimony between the divorced spouses. The analysis of the Guidelines is preceded by the presentation of main views expressed in Polish legal writings with respect to ex-spouses' support obligations. Thus, the author distinguishes four groups of problems: 1) Attention should be focused on the question about the source of support obligations between the ex-spouses. Some authors maintain that such a source should be seen in the very fact of divorce. However, the author subscribes to a prevailing view that the source of the divorced spouses' duty of alimony is their former marriage. The Guidelines support the latter view. 2) Related to the above is the question whether there exists a marital duty of support during the marriage. The author answers in the affirmative. He analyses the marital duty of contribution to the support of the family, (Art. 27 of the Family and Guardianship Code) referring frequently to other views expressed in legal writings. 3) According to Art. 60 of the Family and Guardianship Code, a distinction should be made between a regular and qualified duty of support. A qualified duty of support (Art. 60 § 2 of the Family and Guardianship Code) is vested in a spouse considered to be solely guilty of the breakdown of marriage. The author analyses the premises of a qualified duty of support. In his opinion, the Guidelines have shed light on some important matters. The most important was the explanation of the statutory formula that the innocent spouse, whose material situation deteriorated considerably in consequence of the divorce, may demand that the solely guilty spouse should contribute to the satisfaction of the justified needs of the innocent spouse, even though the latter is not in poverty. 4) In the last part of his article the author considers the premisses of prolonging the 5-year-period of the duty of alimony between innocent spouses (Art. 60 § 3 of the Family and Guardianship Code). 3
Of support obligations between divorced spouses